Key Elements in Latin American Economics Curricula - Rivera Lozada, Isabel Cristina; Meneses Medina, Paula Andrea (Revista Punto Género, 2023)
This research proposes five key elements in the curriculum of economics programmes: situated knowledge, intersectionality, decolonial feminism, critical thinking and gender in order to remedy the historical exclusions that racialized, poor and colonialized women suffer in the economic sphere in the territories of the global south, specifically in Latin America. Starting from the thinking of some authors such as bell hooks, Donna Haraway, María Lugones and Yuderkys Espinosa, with the perspective of decolonial feminism as a backdrop and the gender approach in the curriculum, the problematizing axes propose issues such as labour segregation, the feminization of poverty, wage and income inequality, the care economy, the fetishization and commodification of women, which will be taken into account in the teaching of economic in contexts of the peripheries of the American continent.